PENGARUH PROMOSI ISLAMI DAN KUALITAS PELAYANAN ISLAMI TERHADAP KEPUTUSAN NASABAH MEMILIH TABUNGAN EMAS STUDI PADA PEGADAIAN SYARIAH KABUPATEN GRESIK - Arista Sari, Anjar; Suryaningsih, Sri Abidah (Jurnal Ekonomika dan Bisnis Islam, 2020)
Pegadaian Sharia offers a fexible gold investement product ‘Gold Saving’ which since it was launched in 2015, it has become the most popular. The purpose of this research is to find out the effect of islamic promotion and quality of islamic services to customer’s purchase decision to be customer of Pegadaian Sharia Gold Saving at Gresik Regency. Using multiple linear regression analysis to analyze data and test hypotheses with SPSS version 23. This research model has two independent variables, namely islamic promotion and quality of islamic services, then the model has one dependent variable that is purchase decision. Data were collected by using questioner and measured by likert scale, distributed to 96 respondents of the Gold Saving customer’s of Pegadaian Sharia in Gresik Regency, sample selected using simple random sampling terchnique. The result found that islamic promotion didn’t significant effect to the customer’s purchase decision. Then, the quality of islamic service has positive and significant effect on customer’s purchase decision. However, the result of t-test found these islamic promotion and quality of islamic service has affect in simultaneous on customer’s purchase of Pegadaian Shariah Gold Saving.